Draft genome sequence resource of Erwinia sp. Strain INIA01, a phytopathogen isolated from a diseased stalk of peruvian maize - Estrada Cañari, Richard (2023)
Here, we report the complete genome sequence of Erwinia sp. strain INIA01, a bacterium isolated from lesions of Zea mays from northern Peru. This genome possesses two circular replicons, a 4.2-Mb chromosome, and a 438-kb plasmid.